A detection method of web authentication problems for mobile devices corresponding to IEEE 802.11ac - Sato, Tomoaki; Chivapreecha, Sorawat; Higuchi, Kohji; Moungnoul, Phichet (My University, 2018)
Improvement in the performance of mobile devices makes many opportunities to watch high resolution moving images using a public Wi-Fi LAN service. A web authentication may be required to specify the network user when accessing the public Wi-Fi LAN service. For some authentications, Google, Facebook and Twitter accounts are used. Although the use of these accounts provides convenience, it has serious problems. If the website for the authentication is a phishing site, the account may be abused. The reason is that it is difficult for many users to identify phishing sites. The identification using the CPU of a mobile device has a problem that it cannot deal with the throughput of IEEE 802.11ac. In this article, problems with web authentications used in public Wi-Fi LAN services are surveyed. Then, the authors propose a detection method of the problems that can deal with the throughput realized by IEEE 802.11ac and can process with low-power operations on mobile devices.
Keywords: IEEE 802.11ac; low-power operation; mobile device; web authentication